Amyotrophic lateral sclerosis associated with a pathological expansion in the ATXN7 gene. Issue 5 (3rd July 2022) - Cluse, Florent; Bernard, Emilien; Strubi-Vuillaume, Isabelle; Devos, David; Mouzat, Kevin; Lumbroso, Serge; Froment Tilikete, Caroline; Thobois, StÉphane; Pegat, Antoine
Abstract: Spinocerebellar ataxia type 7 (SCA7) is an autosomal dominant hereditary neurodegenerative disease caused by the expansion of a CAG-repeat in the ataxin-7 ( ATXN7 ) gene, usually characterized by progressive cerebellar ataxia and retinal dystrophy. We report the case of a 45-year-old woman presenting with a rapid-onset amyotrophic lateral sclerosis (ALS) phenotype associated with a 39-CAG-repeat expansion in ATXN7 . This patient had neither ataxia nor retinal dystrophy, but she had an oculomotor cerebellar syndrome and a family history suggestive of SCA7. In SCA7, shorter expansions may be associated with less severe and incomplete clinical phenotypes, which could explain the patient's phenotype. Unknown genetic and environmental factors may also influence the patient's phenotype. We suggest that a pathological expansion in ATXN7 should be considered in cases of ALS-like phenotype, particularly when associated with oculomotor abnormalities or a family history of ataxia or blindness.